DESAIN VENDING MACHINE PENYEWAAN KAMAR HOTEL DENGAN MENGIMPLEMENTASIKAN KONSEP FINITE STATE AUTOMATA - Rosadi Rosadi; Yessica Fara Desvia; Lael Kurniawati; Sri Rahayu; Windu Gata (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
The hotel industry will compete in developing their business, one of which is by applying information technology. In addition to designing an information system for business development, a vending machine can also be designed using the concept of finite state automata (FSA). FSA is a computational model with limited memory that has the function of a digital computer, which can accept input, output, temporary storage and is able to make decisions in defining inputs into outputs. The VM penyewaan kamar hotel design will make a new solution for tourists who do not book rooms online, can choose rooms independently through VM and using two payment methods, that is cash and non-cash method payment. The design stage begins with analyzing business processes at a hotel, describing the machine configuration with state diagrams and then designing the VM user interface. So that an output from the machine can be generated in the form of a room key which will then be used to enter the selected room.